Intravenous Methadone for Severe Cancer Pain: A Presentation of 10 Cases. (28th November 2012) - Lossignol, D.; Libert, I.; Michel, B.; Rousseau, C.; Obiols-Portis, M.
Abstract : Purpose . Methadone, a synthetic opioid agonist, is an effective alternative to strong opioids (morphine, hydromorphone, oxycodone, and buprenorphine) and is widely available as an oral formulation. Few data have been published so far on the use of intravenous (i.v.) methadone for the management of severe or refractory cancer pain. Methods . We followed 10 consecutives cancer patients with severe pain, treated with IV methadone. All had advanced disease and had already received strong opioids, some in association with ketamine. Pain was assessed at T0, T24 hours, and at the end of the treatment. Results . All patients benefited from the switch to IV methadone with a reduction of pain on VAS after 24 hours (median: 4/10; range 0–5) until the end of the treatment (all cases <3/10). The median starting dose was 100 mg/day (range 20–400) and the final dose remained stable with a median of 100 mg/day (range 27–700). The median duration of IV methadone was 11 days (range 2–59). No cardiac toxicity had been observed. Conclusions . IV methadone is an effective pain relieving alternative for the treatment of severe cancer pain, especially in refractory pain syndrome. Moreover, we did not observe any toxicity (neurological or cardiac) or any other major side effects and the treatment was overall well tolerated. More extensive comparative studies should be planned.